Real time high resolution magnetic resonance imaging for the assessment of gastric motility disorders - Ajaj, W (Copyright 2004 by Gut, 2004)
Background: The aim of this study was to evaluate whether patients with increased or decreased gastric motility can be differentiated from healthy volunteers by means of real time magnetic resonance imaging (MRI). Patients and methods: Ten healthy volunteers, 10 patients with gastroparesis, and 10 patients with functional pylorospasm/peptic pyloric stenosis underwent real time MRI. All patients were examined on two separate days; once prior to therapy and once after adequate therapy. Antral motility was quantified by calculating the gastric motility index. Results: Patients with gastroparesis showed a lower motility index compared with the reference volunteer group while the mean motility index of the patient group with pylorospasm was more than three times higher than that of the reference value of the volunteer group. However, the gastric motility index in the patient group with gastroparesis increased, and in the group with functional pylorospasm/peptic pyloric stenosis it decreased significantly after therapy. Conclusion: Real time MRI is a reliable tool for assessment of gastric motion. Furthermore, differences in gastric motility index in patients with increased or decreased gastric motility could be evaluated and quantified. Due to the non-invasive character of MRI, this imaging modality may be an attractive alternative to conventional invasive diagnostic tools for gastric motility disorders and therapeutic monitoring.